Cognitive Behavioral Play Therapy to Improve Emotional Regulation in Children With ADHD: A Quasi-Experimental Study - Ayu Pratiwi; Ahmad Abdul Lutfbis; Ahmad Farid Ramadhan; Maratun Nazila (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Attention-deficit/hyperactivity disorder (ADHD) affects children’s academic, social, and emotional functioning, highlighting the need for feasible school-based interventions. This study evaluated the effectiveness of Cognitive Behavioral Play Therapy (CBPT) in improving emotion regulation among elementary school children with ADHD. A quasi-experimental pretest-posttest control-group design was used. Sixteen children aged 6–9 years were recruited through total sampling and allocated to an intervention group (n = 8) or control group (n = 8). The intervention group received eight structured CBPT sessions over seven days in an Indonesian elementary school, whereas the control group continued routine school activities without CBPT. Emotion regulation was assessed using the Emotion Regulation Checklist (ERC). Data were analyzed using paired-samples and independent-samples t-tests. In the intervention group, the mean emotion-regulation score increased from 57,88 at pretest to 73,13 at posttest, representing a statistically significant improvement (p < 0,05), while the control group showed minimal change. The structured activities helped children identify emotions, challenge maladaptive thoughts, practise self-control, and develop adaptive coping strategies through play. These findings indicate that CBPT may be an effective, developmentally appropriate school-based intervention for improving emotion regulation in children with ADHD. Studies with larger samples, multiple schools, and longer follow-up periods are recommended to confirm the findings.